STRESS SYMPTOMS OF STUDENTS WHO COMPLETE LATE THESIS AT THE FACULTY OF TEACHER AND EDUCATION JAMBI UNIVERSITY - Elin Karlina; Akmal Sutja; Affan Yusra (SUJANA: Education and Learning Review, 2023)
The background of this research discusses the symptoms of stress in students who are late in completing their thesis. who claimed to feel depressed, feel sad, confused, have difficulty controlling their emotions, often feel afraid and have trembling or sweaty hands when they want guidance with their supervisor, feel sad and sometimes feel lazy. So the purpose of this study was to reveal the frequency of stress symptoms in students who were late completing their thesis at the Faculty of Teaching and Education, University of Jambi. The limitations of the problem in this study are: this research was conducted on English education students at FKIP UNJA class of 2018. And this research only examines the symptoms of stress experienced by students, namely from mental symptoms such as; loss of self-confidence, blank look and irritability towards others. Emotional symptoms are manifestations of decreased mood such as anxiety, irrational panic attacks, sadness and fear of criticism, and negative views of oneself. Physical symptoms such as; sweaty palms, restlessness, and shaking hands. And behavioral symptoms; sleeping a lot or a little, socially withdrawn, and lazy. The methodology used in this study is to use quantitative research with a descriptive type. Data was obtained by distributing questionnaires as an instrument that was used to respondents, then the data were analyzed using percentages (%). The population of this study is English Study Program students in class of 2018 who are late in completing their thesis. So the sample of this study was students of the English Study Program with a total of 61 people with purposive sampling technique and the population was carried out on class 2018 students at UNJA.The conclusion from this study is that the frequency of stress symptoms in college students is at a "high" level with a percentage of 66%. In detail regarding matters related to the symptoms of stress, namely: Symptoms of metal stress obtain a "moderate" level of frequency, namely with a percentage of 56%. Symptoms of emotional stress get a frequency of "moderate" with a percentage of 58%. Symptoms of physical stress get a frequency of "moderate" with a percentage of 51%. Symptoms of behavioral stress get a frequency of "moderate" with a percentage of 51%. Suggestions for both lecturers and students are expected to be able to anticipate the symptoms of stress experienced by students during the completion of the thesis so that they do not appear. make motivational deadlines so that they can immediately complete their thesis and prepare themselves to follow the thesis writing process.